2020
DOI: 10.1103/physrevb.102.104204
|View full text |Cite
|
Sign up to set email alerts
|

From bulk descriptions to emergent interfaces: Connecting the Ginzburg-Landau and elastic-line models

Abstract: Controlling interfaces is highly relevant from a technological point of view. However, their rich and complex behavior makes them very difficult to describe theoretically, and hence to predict. In this work, we establish a procedure to connect two levels of descriptions of interfaces: for a bulk description, we consider a two-dimensional Ginzburg-Landau model evolving with a Langevin equation, and boundary conditions imposing the formation of a rectilinear domain wall. At this level of description no assumptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…This perturbation may be interpreted as a site-to-site variation of the energy that ϕ needs to overcome in order to change its state. We recently showed that disorder introduced in this way is compatible with the so-called random bond disorder-and translated into a pinning force with short-range correlations acting on the interfaces in the system [30]. This disorder type was shown to describe domain walls in a large family of magnetic materials [15].…”
Section: Emulating Real Experiments To Study Domain Wall Dynamics Numericallymentioning
confidence: 94%
See 3 more Smart Citations
“…This perturbation may be interpreted as a site-to-site variation of the energy that ϕ needs to overcome in order to change its state. We recently showed that disorder introduced in this way is compatible with the so-called random bond disorder-and translated into a pinning force with short-range correlations acting on the interfaces in the system [30]. This disorder type was shown to describe domain walls in a large family of magnetic materials [15].…”
Section: Emulating Real Experiments To Study Domain Wall Dynamics Numericallymentioning
confidence: 94%
“…The subsequent roughness functions (corresponding to cycles 36 to 85) show a high increase at very short distances exactly when the interface seems to be highly pinned. This strong pinning center shifts the region where B(r) can be reasonably fitted with a power-law to larger values of r, [30,1000]. When the interface This protuberance induces an increase of B(r) at short distances (also indicated by an orange arrow in plot II-(d)), and a shift of the fitting region.…”
Section: Domain Wall Geometrymentioning
confidence: 97%
See 2 more Smart Citations
“…It quantifies the variance of the relative displacements of the interface, as a function of the lengthscale r, and inherits the translation invariance in y of the microscopic disorder. For a clean system (F p (y) = 0), we can compute analytically the full time dependence of this correlation for an infinite interface [52,57]:…”
mentioning
confidence: 99%